Necessidade de calagem da cultura do feijão, em solos da microrregião Mata de Viçosa, Minas Gerais. Experimento em casa de vegetação - da Silva Portela , Maria Cristina L; Defelipo, Braz Vitor; Braga , José Mário; Ribeiro , Antônio Carlos (Revista Ceres, 2025)
Samples of nine soils from the «Zona da Mata» region, Viçosa - State of Minas Gerais, received different rates of lime and were planted to bean (Phaseolus vulgaris L. var. ‘Negrito’) under greenhouse conditions.